Distributed Control System in Electrical Heaters of the Public Buildings - Jianhua Ren; Wei Wang; Tingchao Yang (Institute of Advanced Engineering and Science, 2013)
Being with many advantages such as environmental protection, controllable, facilitate measurement etc, electric heating has been promoted actively in some places .For public buildings with huge energy consumption, electric heating intelligent controlling may be the key to achieve energy conservation. In this paper, visual distributed control system (DCS) was presented in electric heating of the public buildings. In this control system, a PC was used as the host, and RS232/485 interface converter was used as serial interface of mutual conversion .Through industrial standard RS485 bus with high reliability and low cost which was the link between the host and many sets of thermostat, a one-to-many communication network was formed. The MCU of the thermostats was ATMega8 microcontroller. Meanwhile, DS18B20 integrated temperature probe was used in temperature sensor .Through the DCS test online,it met the need of each individual heating unit. Therefore, unnecessary heat waste was reduced, heating costs were saved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2660